Association Between H. pylori Infection and Colorectal Polyps: A Meta-Analysis of Observational Studies - Lu, Depeng; Wang, Mingyu; Ke, Xiquan; Wang, Qiangwu; Wang, Jianchao; Li, Dapeng; Wang, Meng; Wang, Qizhi (Frontiers in Medicine, 2022)
Background: It has been suggested that H. pylori infection is associated with hypergastrinemia and proliferation of colorectal mucosa via direct stimulation, dysbiosis of the gut microbiome and changes in the gut microbiome, all of which may lead to the formation of colorectal polyps. However, consensus remains lack regarding whether H. pylori infection is independently associated with colorectal polyps and whether the association differs according to histological type of colorectal polyps. To summarize the current evidence regarding the relationship between H. pylori infection and colorectal polyps, we conducted a meta-analysis of related observational studies according to the histological types of colorectal polyps. Methods: Observational studies investigating the association between H. pylori infection and colorectal polyps using multivariate analyses were included by search of PubMed, Embase, and Web of Science. A random-effects model was adopted to combine the results. Results: Seventeen studies including 322,395 participants were analyzed. It was shown that H. pylori infection was independently associated with overall colorectal polyps (odds ratio [OR]: 1.67, 95% confidence interval [CI]: 1.24 to 2.24, P < 0.001; I2 = 73%). According to the histological type of colorectal polyps, H. pylori infection was independently associated with adenomatous polyps (OR: 1.71, 95% CI: 1.47 to 1.99, P < 0.001; I2 = 86%), advanced adenomatous polyps (OR: 2.06, 95% CI: 1.56 to 2.73, P < 0.001; I2 = 0%), and hyperplastic polyps (OR: 1.54, 95% CI: 1.02 to 2.30, P = 0.04; I2 = 78%). Evidence based on only one study showed that H. pylori infection was not associated with sessile serrated polyps (OR: 1.00, 95% CI: 0.93 to 1.07, P = 0.99). Conclusions: Current evidence from case-control and cross-sectional studies suggested that H. pylori infection was independently associated with colorectal adenomatous polyps, advanced adenomatous polyps, and hyperplastic polyps, but not with sessile serrated polyps. These findings suggested H. pylori infection may be a possible risk factor of colorectal polyp, which is important for the prevention of colorectal polyp in adult population.